Community attributes reflecting the zooplankton secondary production: using field and experimental approaches - Juliana Deo Dias; Nadson Ressye Simões; María Rosa Miracle; Thais Xavier de Melo; Claudia Costa Bonecker (Acta Limnologica Brasiliensia)
Abstract Aim We investigated the relationship between ecological attributes of the zooplankton community and its secondary production. Methods Samples were taken from lakes in the floodplain of the Upper Paraná River (Brazil), in low and high-water periods, and in a manipulative experiment realized in mesocosms. Results The highest amount of production was related to the dominance of few species. Secondary production of larger and long-lived organisms, such as copepods, had been most associated with the biomass, whereas smaller ones, such as rotifers, with the abundance. Conclusions These attributes of the zooplankton community (biomass and abundance) can be used as proxies to estimate the zooplankton secondary production in the floodplain, supporting the studies on monitoring and conservation of these ecosystems.